Exposure to heavy metals alters the surface topology of alveolar macrophages and induces respiratory dysfunction among Indian metal arc-welders. (December 2018) - Moitra, Subhabrata; Ghosh, Jayashree; Firdous, Jannatul; Bandyopadhyay, Arghya; Mondal, Monojit; Biswas, Jayanta Kumar; Sahu, Subhashis; Bhattacharyya, Soumya; Moitra, Saibal
Background: Despite the available clinico-epidemiological evidence of heavy metal-associated respiratory health hazards among metal arc-welders, experimental confirmation of such an association is lacking. Methods: In this study, we recruited 15 metal arc-welders and 10 referent workers without direct exposure. We assessed respiratory health through a questionnaire and spirometry; estimated manganese, nickel and cadmium levels in blood, urine and induced sputum; performed differential counts of sputum leucocytes and measured plasma malondialdehyde (MDA). We used atomic force and scanning electron microscopy to assess the physical property of the alveolar macrophages (AMs) obtained from induced sputum and analysed cell surface deposition of heavy metals using energy dispersion X-ray analysis (EDX). Sputum cellular DNA damage was assessed by DNA-laddering assay. Results: There was a higher body burden of manganese and nickel in the metal arc-welders than the referents. Among major spirometric indices, only the forced mid-expiratory flow rates (FEF25–75 ) were reduced in the welders compared with the referents (63.4 ± 14.7 vs. 89.2 ± 26.7, p < 0.01); this reduction was associated with both heavy metal levels ( β : −41.8, 95% CI: −78.5% to −5.1%) and plasma MDA (−0.37; −0.68 to −0.06). In metal arc-welders, significant physical and morphological changes were observed in AMs through microscopic evaluation while EDX analyses demonstrated higher deposition of heavy metals on the AM cell surface than the referents. We also observed a higher degree of DNA damage in the sputum cells of the exposed workers than the referents. Conclusion: Heavy metal exposure-induced adverse respiratory effects among metal arc-welders are mediated through haematological and cytological interactions.